MHC class II+ cells in the gills of Atlantic salmon ( Salmo salar L.) affected by amoebic gill disease - Morrison, RN; Koppang, EO; Hordvik, I; Nowak, BF (Veterinary Immunology and Immunopathology, 2006)
Amoebic gill disease (AGD) is characterised by the association of Neoparamoeba sp. with hyperplastic gill tissue of affected fishes, however, the identity and role of host cells associated with AGD lesions are not known. Here, we investigated cells with an immunological role that were associated with AGD lesions by locating cellular MHC class II chain. A tank housing Atlantic salmon (Salmo salar) was inoculated with Neoparamoeba sp., and MHC class II chain expression in the gills was qualitatively assessed by immunohistochemistry. In AGD-nave control fish, MHC class II+ cells were detected basolateral to the interlamellar epithelium as well as upon the interlamellar and secondary epithelium. In the gills of AGD affected fish MHC class II+ cells were observed in both affected and unaffected tissue. Within AGD lesions, numerous MHC class II+ cells were present and these cells exhibited variable levels of expression suggesting that like mammals, MHC class II expression is highly regulated. The presence of MHC class II+ cells within gill lesions is indicative of immune cell trafficking and these cells could contribute in an antigen presentation capacity to the development of an antibody response in fish chronically affected by AGD. 2005 Elsevier B.V. All rights reserved.